A critical evaluation of venous thromboembolism risk assessment models used in patients with lower limb cast immobilisation. Issue 3 (September 2016) - Watson, Ultan; Hickey, Ben A.; Jones, Huw M.; Perera, Anthony
Highlights: Of the risk assessment models assessed, two demonstrated limited clinical utility. The most accurate RAM could miss one in two sVTEs. Limb immobilisation should not be an absolute VTE risk factor for patients in a cast. Abstract: Background: There is a recognised link between lower limb cast immobilisation and the development of venous thromboembolism (VTE). Our aim was to assess the diagnostic accuracy of risk assessment models (RAMs) applicable to this patient group. This has not been done before. Methods: A literature and guideline review identified five RAMs. They were used to retrospectively risk assess a consecutive series of patients who were diagnosed with symptomatic VTE following lower limb injury treated with a cast (Group I). A case-matched cohort who did not suffer symptomatic VTE (Group II) was also retrospectively risk assessed. The RAMs' diagnostic performance indicators were calculated. Results: Groups I and II consisted of 21 patients each. There was no significant difference in the mean age or total number of VTE risk factors between Groups I and II ( p  = .957 and p  = .878 respectively). The Plymouth (2010) RAM achieved the highest accuracy (54.8%). Conclusions: Each RAM demonstrated significant limitations. Two displayed very limited clinical utility. Three recommended chemical thromboprophylaxis to all patients because they weighted lower limb immobilisation as an absolute risk factor for the development of VTE. Cast immobilisation should not be considered an absolute risk factor when risk assessing patients who all have casts. Prospective evaluation with a larger patient cohort is required.